Covid-19 Pandemic and Transformation of Organizational Culture in Universities - Abraham Partogi Pardamean Tambunan; Mustain Mashud; Septi Ariadi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Changes in organizational culture within the scope of universities caused by the COVID-19 pandemic are the focus of this study. Currently, there are 2 choices of work arrangement, namely: Work from Home (WFH), and working offline at the workplace. As such, changes in the values ​​adopted by members of the organization or in organizational culture are expected. This study focuses on the influence of organizational culture in universities on the performance of organizational members who are lecturers, teaching staff, and other elements. Each member of the organization has a different view and ways of responding to the reality of changing organizational culture during this COVID-19 pandemic. Differences in roles in the organization can be a factor in the differing opinion. A lecturer during the WFH period must carry out teaching and learning activities and conduct online meetings. While other staff who take care of administration are faced with different kinds of online work. Consequently, these staff from different roles may have a different view. This study aims at understanding how organizational culture in universities today can affect the performance of organizational members in the post-COVID-19 pandemic and other elements. The result shows that universities are organizations that have been heavily affected by the COVID-19 pandemic. It has transformed their culture from various directions, from academic activities, administrative, up to the social value order.